Groundwater for drinking and sustainable agriculture and public health hazards of nitrate: Developmental and sustainability implications for an arid aquifer system - Boualem Bouselsal; Adel Satouh; Johnbosco C. Egbueri; Mofreh A. Hashim; Ahmed A. Arafat; Prabhu Paramasivam; Ali Alzaed; Enas E. Hussein (Results in Engineering)
This study evaluates groundwater quality in the Lower Cretaceous Aquifer (LCA) of Timimoun, Algeria, for drinking and agricultural uses, focusing on geochemical influences on water mineralization and public health risks. A total of 44 groundwater samples were analyzed for physicochemical parameters, including pH, major ions (Ca2+, K+, Na+, Mg2+, SO42−, Cl−, NO3−, HCO3−) total dissolved solids (TDS), and electrical conductivity (EC). The Water Quality Index (WQI) categorized the groundwater as good (54.54 %), poor (31.82 %), very poor (9.09 %), and unsuitable for drinking (4.55 %). Agricultural suitability was assessed using metrics such as Sodium Adsorption Ratio (SAR), Sodium Percentage (Na%), and Permeability Index (PI), revealing a range from permissible to doubtful irrigation quality. Examination of Gibbs and Piper plots and relationships between major elements, alongside the calculations for saturation indices of key minerals, revealed the groundwater was weakly alkaline with dominant Ca-Mg-Cl and Na-Cl hydrogeochemical types in the LCA water. The processes of evaporite and silicate minerals dissolution and cationic exchange were the dominant mechanisms behind the ion generation. Notably, Nitrate concentrations (9–80 mg/L) exceeded safe limits in 29.54 % of samples, posing significant health risks, especially to infants and children, with Hazard Quotient (HQ) values exceeding 1 in 97.73 % of infants, 95.45 % of children, and 45.54 % of adults. The integration of the water quality index, health risk assessments, hydrogeochemical modeling, and GIS mapping provides a comprehensive framework for analyzing groundwater in arid regions under pressure from climate change and human activities. These findings highlight the need for integrated strategies for sustainable groundwater management worldwide.